Bio-based enzymes as source of chemicals and materials in industrial biotechnology - Shaari Majed, Muhammad Amer Daneal; Abdullah, Dzul Izlee; Mohamed, Elizah; Abd Aziz, Mohd Haiqal (Penerbit UTHM, 2022)
Bio-based enzymes application is one of the most reliable methods or processes used in biotechnological processes. Most of the industrial processes nowadays have a poor effect on the environment and make the current climate and conditions in the world worst. Most industrial companies and manufacturers are moving towards a sustainable environment and ensuring that they do not harm the environment. By switching to biotechnology, the value of biotechnology can be made known and sustainable industrial development can be achieved. Biotechnology is involved in many sectors, including chemical, food processing, textiles, mining, materials, and energy. Bio-based processes involving enzymes such as lignin peroxidase (LiP), manganese peroxidase (MnP) and laccase of white-rot fungi (WRF) are used instead of chemical products and substances to achieve the same outcome from the same industrial degradation, decolourization or even detoxification processes. By chance, biotechnological processes also provide tools for adapting and modifying biological organisms, products, processes, and systems found in nature to help develop more profitable, eco-friendly and eco-efficient processes. Chemical and related industries are transforming from conventional chemical-based models to a greener, more efficient and more environmentally friendly catalytic alternative, both at the laboratory and industrial scale. Bio-based catalysis provides many advantages in this sense, along with possible biotechnological and environmental applications. Empowering the industry with growing resources also helps increase cost and environmental efficiency beyond traditional chemical technologies.